Prevalence, Awareness, and Understanding of Pelvic Floor Disorders in Adolescent and Young Women. Issue 5 (September 2016) - Parden, Alison M.; Griffin, Russell L.; Hoover, Kimberly; Ellington, David R.; Gleason, Jonathan L.; Burgio, Kathryn L.; Richter, Holly E.
Abstract : Objectives: The objective of this study was to characterize symptom prevalence, awareness of pelvic floor disorders (PFDs) in family/friends, and understanding of factors contributing to the development of PFDs in women aged 19 to 30 years. Methods: This study is a cross-sectional study via online questionnaire survey of female students aged 19 to 30 years enrolled at the University of Alabama at Birmingham. Results of "adolescent women" aged 19 to 24 years were compared with "young women" aged 25 to 30 years. Results: A total of 1092 questionnaires were completed with the mean age being 23.5 ± 3.1 years. The overall rate of urinary incontinence (UI) was 10.3% without a difference between adolescent and young women ( P = 0.61). There were no differences in rates of urgency UI ( P = 0.061), stress UI ( P = 0.29), or pelvic organ prolapse (POP) symptoms ( P = 0.56) between groups. There was no difference between groups in awareness of family members with UI, fecal incontinence (FI), or POP symptoms ( P ≥ 0.24). However, logistic regression showed that the young women were more likely to have received education regarding UI (adjusted odds ratio [aOR], 2.6; 95% confidence interval [CI], 1.8–3.6), FI (aOR, 3.3; 95% CI, 2.2–4.8), POP (aOR, 2.9; 95% CI, 2.1–4.2), and have greater understanding regarding causes of UI (aOR, 2.9; 95% CI, 1.7–4.8), FI (aOR, 1.6; 95% CI, 1.1–2.3), and POP (aOR, 1.9; 95% CI, 1.3–2.9). Conclusions: Women aged 25 to 30 years had more awareness and understanding of PFDs compared with adolescent women. These data may have implications for primary prevention strategies of PFDs. Abstract : Women ages 25-30 had more awareness and understanding of pelvic floor disorders compared to adolescent females.Supplemental digital content is available in the text.